Prevalence of mental disorders among people with opioid use disorder: A systematic review and meta-analysis - Santo, Thomas; Campbell, Gabrielle; Gisev, Natasa; Martino-Burke, Daniel; Wilson, Jack; Colledge-Frisby, Samantha; Clark, Brodie; Tran, Lucy Thi; Degenhardt, Louisa (Drug and alcohol dependence, 2022)
Opioid use disorder (OUD) and mental disorders are major public health issues and comorbidity is common. Among people with OUD, comorbid mental disorders are associated with poorer health outcomes. To our knowledge, this is the first systematic review and meta-analysis to estimate prevalence of specific mental disorders among people with OUD. We searched Embase, MEDLINE, and PsycInfo from 1990 to 2021 for observational studies of depression, anxiety, post-traumatic stress disorder (PTSD), bipolar, personality, and other pre-specified mental disorders among people with OUD. We pooled current and lifetime estimates of each disorder using random-effects meta-analyses with 95% Confidence Intervals (CIs). Meta-regressions and stratified analyses were used to assess heterogeneity of prevalence estimates by methodological factors and sample characteristics. Of the 36,971 publications identified, we included data from 345 studies and 104,135 people with OUD in at least one pooled estimate. Among people with OUD, the prevalence of current depression was 36.1% (95%CI 32.4–39.7%), anxiety was 29.1% (95%CI 24.0–33.3%), attention-deficit/hyperactivity disorder was 20.9% (95%CI 15.7–26.2%), PTSD was 18.1% (95%CI 15.4–20.9%), and bipolar disorder was 8.7% (95%CI 6.7–10.7%). Lifetime prevalence of anti-social personality disorder was 33.6% (95%CI 29.1–38.0%) and borderline personality disorder was 18.2% (95% CI 13.4–23.1%). Sample characteristics and methodological factors, including sex, were associated with variance of multiple prevalence estimates. Our findings emphasise the need for access to mental disorder treatment among people with OUD. Specific mental disorder estimates may inform clinical guidelines, treatment services, and future research for people with OUD, including subpopulations with distinct treatment needs. •We estimated prevalence of mental disorders among people with OUD.•Depression (36%), anxiety (29%), & PTSD (18%) were common.•Prevalence of anti-social (34%) & borderline personality disorder (18%) was high.•ADHD (21%), bipolar disorder (9%), dysthymia (7%), & OCD (7%) were also examined.•Depression, anxiety, and PTSD was more common among women.